Determinants of inequalities in life expectancy: an international comparative study of eight risk factors - Johan P Mackenbach, ProfPhD; José Rubio Valverde, MSc; Matthias Bopp, PhD; Henrik Brønnum-Hansen, PhD; Patrick Deboosere, ProfPhD; Ramune Kalediene, ProfPhD; Katalin Kovács, PhD; Mall Leinsalu, PhD; Pekka Martikainen, ProfPhD; Gwenn Menvielle, PhD; Enrique Regidor, PhD; Wilma J Nusselder, PhD (Elsevier, 2019)
Summary: Background: Socioeconomic inequalities in longevity have been found in all European countries. We aimed to assess which determinants make the largest contribution to these inequalities. Methods: We did an international comparative study of inequalities in risk factors for shorter life expectancy in Europe. We collected register-based mortality data and survey-based risk factor data from 15 European countries. We calculated partial life expectancies between the ages of 35 years and 80 years by education and gender and determined the effect on mortality of changing the prevalence of eight risk factors-father with a manual occupation, low income, few social contacts, smoking, high alcohol consumption, high bodyweight, low physical exercise, and low fruit and vegetable consumption-among people with a low level of education to that among people with a high level of education (upward levelling scenario), using population attributable fractions. Findings: In all countries, a substantial gap existed in partial life expectancy between people with low and high levels of education, of 2·3-8·2 years among men and 0·6-4·5 years among women. The risk factors contributing most to the gap in life expectancy were smoking (19·8% among men and 18·9% among women), low income (9·7% and 13·4%), and high bodyweight (7·7% and 11·7%), but large differences existed between countries in the contribution of risk factors. Sensitivity analyses using the prevalence of risk factors in the most favourable country (best practice scenario) showed that the potential for reducing the gap might be considerably smaller. The results were also sensitive to varying assumptions about the mortality risks associated with each risk factor. Interpretation: Smoking, low income, and high bodyweight are quantitatively important entry points for policies to reduce educational inequalities in life expectancy in most European countries, but priorities differ between countries. A substantial reduction of inequalities in life expectancy requires policy actions on a broad range of health determinants. Funding: European Commission and Network for Studies on Pensions, Aging, and Retirement.